Community participation disparities among people with disabilities during the COVID-19 pandemic. - Kersey, Jessica; Lane, Rachel; Kringle, Emily A.; Hammel, Joy (Disability & Rehabilitation, 2025)
Purpose: To describe disparities in community participation during the COVID-19 pandemic among people with disabilities. Methods: Respondents to Phase 3.3 of the COVID Household Pulse Survey (US Census Bureau) were classified by disability status. Risk ratios and risk differences were computed to compare the risk of poor outcomes on economic participation, community service use, and community activities by disability status - both overall (compared to the nondisabled reference) and by race/ethnicity (each subgroup compared to the White nondisabled reference). Results: At least one type of disability was reported by 59.6% of respondents. People with disabilities were more likely to report in-person medical appointments but were at greater risk of poor outcomes across all other outcomes [risk ratio range = 1.01(1.01–1.02) to 1.91(1.80–2.01), risk difference range = 1.0(0.5–1.5) to 13.4(12.6–14.2)]. The disabled Black and disabled Hispanic/Latino groups experienced disproportionately high risk of poor outcomes across all indicators [risk ratio range = 1.0 (1.0–1.1) to 6.1 (5.0–7.1), risk difference range = 3.2 (1.9–4.4) to 33.1 (30.1–35.4)]. Conclusions: The high number of people reporting disability, along with the notable disparities in community participation outcomes among those reporting disability, suggest the need for expanded rehabilitation services and community supports to enhance participation. IMPLICATIONS FOR REHABILITATION: People with disabilities experienced disparities in community participation outcomes during the pandemic, particularly in indicators of economic participation (paid employment, income, and education). Disabled people from racial and ethnic minority groups experienced the most severe disparities in outcomes. Stronger rehabilitation services are critical to address new disability or pandemic-related changes in the experience or severity of existing disability. Stronger community and social supports (employment supports, accessible assistive technology, and safe transportation options) may also reduce the disparities in community participation experienced by people with disabilities.